1996
DOI: 10.1074/jbc.271.2.707
|View full text |Cite
|
Sign up to set email alerts
|

Members of the Caudal Family of Homeodomain Proteins Repress Transcription from the Human Apolipoprotein B Promoter in Intestinal Cells

Abstract: Apolipoprotein B (apoB) is the major protein component of low density lipoproteins, and plays a central role in cholesterol transport and metabolism. The apoB gene is transcribed in the liver and in the intestine in humans. Although much is known about the DNA sequence elements and protein factors that are important for transcription of the human apolipoprotein B gene in the liver, less is known about the mechanisms that control transcription of this gene in the intestine. The sucrose isomaltase gene (SI), is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…The normal actions of HNF-1␣ include enhancing the transcription of apo B [23][24][25] and suppressing the transcription of apo AI. 27 Thus, in subjects with type 2 diabetes, the lower plasma total and LDL cholesterol and apo B levels would also be consistent with transactivational loss of function of the HNF1A S319 product.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The normal actions of HNF-1␣ include enhancing the transcription of apo B [23][24][25] and suppressing the transcription of apo AI. 27 Thus, in subjects with type 2 diabetes, the lower plasma total and LDL cholesterol and apo B levels would also be consistent with transactivational loss of function of the HNF1A S319 product.…”
Section: Discussionmentioning
confidence: 99%
“…20 -22 The HNF1A gene product, HNF-1␣, is a transcriptional activator of several hepatic genes, including albumin, ␣1-antitrypsin, and ␣-and ␤-fibrinogen. 21,22 In addition, HNF-1␣ was shown to enhance transcription of apolipoprotein (apo) B [23][24][25] and apo(a) 26 and to downregulate transcription of apo CIII and apo AI. 27 Because it regulates the transcription of several apolipoprotein genes, it is possible that naturally occurring mutations in HNF-1␣ could affect plasma lipoprotein metabolism.…”
mentioning
confidence: 99%
“…Gel Retardation Assays-COS cells were transfected (as described above) with 10 g of expression plasmids for either CDP (pMT2.CDP), C/EBP-␣ (pMSV.C/EBP␣), or HNF-1␣ (pGEM.HNF-1␣), and cellular lysates enriched for these proteins were prepared as described previously (20). Binding sites for transcription factors CDP, HNF-1␣, and C/EBP␣ were identified within CYP7A1 intron 1, using the online TRANSFAC 3.5 data base sequence search and analysis service (21).…”
Section: Methodsmentioning
confidence: 99%
“…It remains to be determined whether homeodomain transcription factors that recognize TAAT elements in neural cells act as transrepressor proteins or whether they act as transactivators that compete for binding to the same elements with nonhomeodomain-type repressor proteins. Although many homeodomain transcription factors function as transactivator proteins to stimulate transcription of target genes, it has been shown that a number of homeodomain proteins act as transcriptional repressors on the promoter of neural (40)(41)(42)(43)(44)(45) as well as nonneural genes (46)(47)(48). Evidence indicates that these proteins are composed of modular domains, some of which mediate activation whereas others mediate repression (46,(49)(50)(51).…”
Section: Mol Endo · 1998mentioning
confidence: 99%